A Narrative Critique of The Saami Bear Myth - Lidström, Per-Gunnar (2019)
The Saami bear myth has in the research been closely tied to the bear hunting ritual. When the ritual has been discussed the myth has been narrated and after that the researcher has continued with the bear hunt. There has not yet been a thorough analysis of these bear myths. In this thesis five Saami bear myths are analysed with narrative criticism. They are written down by Pehr Fjellström, Sigrid Drake, Johan Olafsson Turi and Harald Grundström. A shortened plot of the narratives is: a Saami girl lives together with a bear and they get a son. A dialogue is had between the bear and his family where information is given from the bear, later the bear is killed. Conflict between a bear family member and the hunters and the meat is shared. This study explores the information about the relationship between the Saamis and the bear that can be drawn from these myths. Two of my findings are that the conflicts between the hunters and the family member of the bear is often won by the family member with aid from the bear. The importance of the sharing of the bear meat is featured in all of the versions of the myths; if the bear meat is not shared by the hunters, the bear comes alive and none of them gets a piece.